Pembentukan Desa Sadar Hukum Dan Perlindungan Hukum Terhadap Perempuan Dan Anak Di Desa Sumingkir Kecamatan Kutasari Kabupaten Purbalingga - Endang Eko Wati; Sugeng Riyadi; Fetri Fatorina (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Consistent law enforcement must not only come from the aspect of the government as law enforcement officials, but also from people who are aware of and obey the law. For some people, to create legal awareness in the community, it is enough to provide information in the form of counseling or campaigns. But that's not enough. At least, besides campaigning, there are three other additional ways that must be done so that people have legal awareness, namely setting an example, providing legal knowledge, providing rewards or legal action. The method used is observation and active participation through the FGD forum. The results of Community Service obtained are that a legally aware family in Sumingkir Village has been formed and has an SK from the Government of Purbalingga Regency. The community is enthusiastic to learn and develop legal awareness activities in daily life. The formation of a law-aware family in Sumingkir Village is expected to increase awareness of the legal regulations that apply in society. The community wants to work shoulder to shoulder in solving problems dealing with the law. People are no longer afraid when they have to deal with the law. The debriefing material related to legal, sexual violence against women and children, women in the Islamic version is expected to be a provision that supports the realization of a law-aware society.